LICHEN DIVERSITY IN KEBUN RAYA BANUA, BANJARBARU CITY, SOUTH KALIMANTAN PROVINCE - Puspita Sari, Alifia; Prasetyo, Opik; Muhammad Abdi Gusti (Indonesian Biodiversity Journal, 2025)
Lichen are pioneer organisms resulting from symbiosis between mycobionts (fungi) and photobionts (algae or cyanobacteria) that play an important role in maintaining ecosystem balance. This study aims to determine the diversity of lichen species in the Kebun Raya Banua, Banjarbaru City, South Kalimantan Province and to analyze the environmental factors that influence their existence. The study was conducted using an exploratory survey method with a purposive sampling technique at three observation stations, and diversity analysis was calculated using the Shannon–Wiener Index (H'). The results showed that 7 lichen species belonging to 6 families were found, namely Cryptothecia striata, Graphis scripta, Diorygma sticticum, Dirinaria applanata, Phlyctis argena, Lepraria sp., and Bacidia sp., with a total of 110 colonies and a diversity index value of Ĥ = 1.8233 which is included in the moderate diversity category. These values indicate that environmental conditions in the Kebun Raya Banua are still quite stable and support the growth of various types of lichen, with temperature, humidity, soil pH, and light intensity as important factors influencing variations in diversity between observation stations.